LEGAL POLICY ON PREVENTING ENVIRONMENTAL DAMAGE TO PEATLANDS IN THE CONTEXT OF ACHIEVING SUSTAINABLE DEVELOPMENT - Ambok Asse; Sunardi Sunardi; Diyan Isnaeni (JCH (Jurnal Cendekia Hukum), 2025)
Peatland management has become a crucial issue, and it is necessary to examine the complexity of peatland issues through research that prioritizes environmental protection. The research method used in this study is normative research (doctrinal legal research). The data collection technique used is a literature study. The data obtained was analysed qualitatively and normatively. The findings indicate that there are numerous regulations governing peatlands, ranging from the most general to the most specific. However, the implementation of these regulations remains uneven, as evidenced by the continuing damage to the peatland environment. There is a need for firm legal action, both in terms of normative and administrative regulations. The political configuration of law in preventing environmental damage to peatlands can be realised through sustainable development. Nevertheless, a democratic political configuration of law is needed, imposing restrictions on government actions to protect individuals and groups, with the aim of safeguarding indigenous peoples or communities that already have systems and regulations in place for their environment. The direction of legal policy in efforts to prevent environmental damage to peat ecosystems can be through explicit regulations, providing certainty to indigenous peoples through the Indigenous Peoples Act, agrarian reform, and stopping the seizure of peatlands in the name of whatever it may be.